Fast seamless joining of SiCw/Ti3SiC2 composite using electric field‐assisted sintering technique. Issue 5 (1st June 2021) - Zhou, Xiaobing; Shi, Lin‐Kun; Zou, Shunrui; Xu, Jie; Liu, Yihe; Tatarko, Peter
Abstract: A pair of Ti3 SiC2 reinforced with SiC whiskers (SiCw /Ti3 SiC2 ) composites was successfully joined without any joining materials using electric field‐assisted sintering technology at a temperature as low as 1090°C ( T i ) and a short time of 30 s. The microstructure and mechanical properties of the obtained SiCw /Ti3 SiC2 joints were investigated. The solid‐state diffusion was the main joining mechanism, which was facilitated by a relatively high current density ( 586 A/cm 2 ) at the joining interface. The shear strength of the sample joined at 1090°C was 51.8 ± 2.9 MPa. The sample joined at 1090°C failed in the matrix rather than at the interface, which confirmed that a sound inter‐diffusion bonding was obtained. A rapid and high efficient self‐joining process may find application in the case of SiCw /Ti3 SiC2 sealing cladding tube and end cap.